1998
DOI: 10.1002/(sici)1097-0142(19980901)83:5<858::aid-cncr9>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastasis and tumor cell microinvolvement of lymph nodes from esophageal squamous cell carcinoma

Abstract: The results of the current study show that, in SCC of the esophagus, MM, but not TCM, in the regional lymph nodes is prognostically equivalent to metastasis and should be examined by immunohistochemistry to classify these cases correctly as pN1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 15 publications
4
93
1
1
Order By: Relevance
“…In gastric cancer, Isozaki et al [25] and Natsugoe et al [26] reported that lymph node micrometastases were identified in 10-30% of specimens by step sectioning or IHC. Our results were similar to these studies, and 13% of patients diagnosed with no metastasis by H&E staining were judged lymph node positive by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, Isozaki et al [25] and Natsugoe et al [26] reported that lymph node micrometastases were identified in 10-30% of specimens by step sectioning or IHC. Our results were similar to these studies, and 13% of patients diagnosed with no metastasis by H&E staining were judged lymph node positive by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,13 Recently, immunohistochemical assays for epithelialspecific antigens such as cytokeratins and genetic diagnostic procedures such as the RT-PCR method have been used to detect micrometastasis in the lymph nodes, blood, and bone marrow. [4][5][6][7] Only one report of leptomeningeal metastasis from lung adenocarcinoma diagnosed by RT-PCR with CEA mRNA has been previously published. 14 In the present case, accurate diagnosis of leptomeningeal carcinomatosis was not made by the cytological examination of the cerebrospinal fluid or by imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…After the slide was washed in Trisbuffered saline (TBS), it was incubated for 60 min at 37°C with the monoclonal antibody cocktail AE1/AE3 (antihuman cytokeratin; Dako, Carpinteria, CA, USA), which is reactive with a broad spectrum of human cytokeratins. 6 After the slide was washed in TBS, it was incubated with peroxidase-labeled polymer conjugated to primary antibody for 30 min. After the slide was again washed in TBS, it was incubated with a substrate chromogen (Fast Red Substrate System; Dako) for 10 min, washed in water, counterstained with hematoxylin, and placed under a coverslip with glycerin gelatin (Glycegel; Dako).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Natsugoe et al 28 demonstrated that micrometastasis, but not ITCs, in the regional lymph nodes in esophageal squamous cell carcinoma is prognostically equivalent to metastasis and these cases should be examined by immunohistochemistry to classify them correctly as pN1. In particular, the prognostic value of SN micrometastases detected by reverse transcriptase-polymerase chain reaction (RT-PCR) is still controversial.…”
Section: Clinical Impact Of Micrometastasis Isolated Tumor Cells Anmentioning
confidence: 99%